2021
DOI: 10.3390/vaccines9060635
|View full text |Cite
|
Sign up to set email alerts
|

Specific Treatment Exists for SARS-CoV-2 ARDS

Abstract: The COVID-19 pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), seems to be difficult to overcome. A pandemic of such a scale has not been seen since the 1918 influenza pandemic. Although the predominant clinical presentation is respiratory disease, neurological manifestations and sequelae are increasingly being recognized. We observed a case series of rapid recovery of ARDS within 24 h in the preliminary clinical features of COVID-19 ARDS-associated neurological disease. It was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…Other approaches supporting the redox state include nano-carriers that deliver antioxidant enzymes (such as MSR) to vascular cells [ 106 ], arginine supplementation [ 23 ], the ingestion of encapsulated glutathione (GSH) [ 91 , 107 , 108 ], or indirect increase in glutathione production via vitamin D supplementation [ 109 ]. Reduced ARDS incidence and death of COVID-19 patients were reported after treatment with Dapsone, an amino-sulfone analogue of methionine oxidation products that competes with the inflammasome [ 110 ]. The above studies showcase the potential of amine-related targets to support the immune system, reduce the severity of COVID-19 and improve the survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches supporting the redox state include nano-carriers that deliver antioxidant enzymes (such as MSR) to vascular cells [ 106 ], arginine supplementation [ 23 ], the ingestion of encapsulated glutathione (GSH) [ 91 , 107 , 108 ], or indirect increase in glutathione production via vitamin D supplementation [ 109 ]. Reduced ARDS incidence and death of COVID-19 patients were reported after treatment with Dapsone, an amino-sulfone analogue of methionine oxidation products that competes with the inflammasome [ 110 ]. The above studies showcase the potential of amine-related targets to support the immune system, reduce the severity of COVID-19 and improve the survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Dapsone may have achieved this through a competitive therapeutic mechanism to counter the progression of MCI to AD ( Lee et al., 2020b , 2021 ). This study explains that dapsone acts to inhibit the neuroinflammasome and ubiquitination stochastically by the flow of electrons ( Lee et al., 2020a ; Kanwar et al., 2021 ). ( Figure 4 )
Figure 4 Anticatalysis schematic diagram: blocking of the neuroinflammasome by Dapsone( Lee et al., 2020a ) Dapsone is a myeloperoxidase inhibitor.
…”
Section: Discussionmentioning
confidence: 87%
“…However, similar studies the following year showed no difference in discovering senile plaques between the patient and control groups ( Namba et al., 1992 ; Kimura and Goto, 1993 ; Goto et al., 1995 ). Therefore, we hypothesized that the lack of an effect of antileprosy drugs in preventing AD and Aβ neurotoxicity ( Endoh et al., 1999 ) should be a null hypothesis ( Lee et al., 2020b ; Kanwar et al., 2021 ). A pilot cohort study on dapsone was conducted from 2008 to 2020 and demonstrated recovery from AD to MCI ( Lee et al., 2020b , 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in response to requests from patients and their families, we acceded to their entreaties "to try anything that might help" by discussing the potential risks and possible benefit of several untested, unproven treatments and anecdotal reports that have been published recently. This includes the published discussions of experience with, and rationale for, dapsone in the COVID-19 disease [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%